2022
DOI: 10.3389/fnut.2022.905006
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Postharvest Browning in Rambutan Fruit by Melatonin Is Associated With Inhibition of Phenolics Oxidation and Reinforcement of Antioxidative Process

Abstract: Rambutan is a famous tropical fruit with a unique flavor and considerable economic value. However, the high vulnerability to postharvest browning leads to a short shelf life of rambutan fruit. Melatonin (MT) is an excellent bioactive molecule that possesses the potential to improve the storability of the harvested crops. In this study, the physiological mechanism of exogenous MT in affecting pericarp browning and senescence of postharvest rambutan fruit was investigated. Experimental results showed that the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Xiao et al [ 92 ] reported that MT treatment significantly downregulated the expression of PPO (PPO1, PPO2, PPO3, and PPO4) and POD (POD1, POD4, POD72, and POD-N) genes in fresh-cut taro. Wei et al [ 93 ] found that MT treatment helps protect against subcellular decompartmentalization in rambutan pericarp, thereby reducing enzymatic browning. Magri et al [ 86 ] reported that LOX-driven lipid peroxidation produces MDA and H 2 O 2 , leading to cellular degradation and fruit discoloration.…”
Section: Resultsmentioning
confidence: 99%
“…Xiao et al [ 92 ] reported that MT treatment significantly downregulated the expression of PPO (PPO1, PPO2, PPO3, and PPO4) and POD (POD1, POD4, POD72, and POD-N) genes in fresh-cut taro. Wei et al [ 93 ] found that MT treatment helps protect against subcellular decompartmentalization in rambutan pericarp, thereby reducing enzymatic browning. Magri et al [ 86 ] reported that LOX-driven lipid peroxidation produces MDA and H 2 O 2 , leading to cellular degradation and fruit discoloration.…”
Section: Resultsmentioning
confidence: 99%
“…The thiobarbituric acid colorimetry method was used to measure MDA content ( Wei et al., 2022 ). Briefly, a total of 1.0 g of pulp sample was homogenized with 5 mL of 5% trichloroacetic acid (TCA) solution, and then centrifuged at 10,000 × g for 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Taking together the results for ripening quality parameters, it could be inferred that melatonin delayed the cherimoya postharvest ripening process during storage, due to delayed ethylene production, as previously reported by other treatments, such as shock CO 2 treatments for three days [ 12 ], 500 nL L −1 1-methylcyclopropene (1-MCP) for 16 h [ 41 ] or an edible coating based on carnauba wax [ 50 ]. Furthermore, melatonin has been reported to delay senescence and ripening processes, leading to maintenance of fruit quality properties in guava [ 33 ], rambutan [ 51 ], strawberries [ 52 ] and peaches [ 34 ], among other fruit species. These effects have been attributed to a more efficient system for scavenging reactive oxygen species and reduced membrane lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%